Pengaruh Pelatihan Kerja Dan Motivasi Terhadap Kinerja Karyawan (Studi Kasus pada Karyawan Hotel Grasia Semarang) - Rispati, Firsa` Hadi; Rodhiyah, Rodhiyah; Dewi, Reni Shinta (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to determine the effect of job training and motivation on employee performance Grasia Hotel Semarang. Population of this study is Grasia Semarang Hotel employees totaling 80 people, with the saturated sample or census of all employees are using the hotel as a respondent. Measurement scale using a Likert scale. In the analysis of the data using simple linear regression and multiple regression test with SPSS 16.0. From the analysis of the data found that the categories of job training that is equal to 51.2 percent declared fit. categories of motivation that is equal to 67.5 per cent said either. Employee Performance category that is equal to 67.5 per cent said either. Effect of job training on the performance of 10.1 percent and motivation affect the performance by 5.0 percent. These results are caused by several factors, including the suitability of this type of training, the salary given by the company, employee absenteeism, as well as the timing of the work. The conclusion that job training has the most effect on the performance of employees is 10.1 percent compared to the motivation that only 5 percent. Taken together job training and motivation has an influence on the performance of employees by 13.3 percent. Advice that can be given, HR management Grasia Hotel Semarang need to pay attention to all matters relating to vocational training, either instructor, materials and schedules, in order to apply the training to be better targeted and become more leverage. Companies need to improve employee motivation it can be done with greater incentives and increased comfort facilities such as toilets and canteen are intended for employees.